What Is This Thing Called Evaluation Theory? - Sebastian Lemire; Bianca Montrosse-Moorhead; Christina Christie (Journal of MultiDisciplinary Evaluation)
Background: Evaluation theory has and continues to play an important role in the practice and profession of evaluation. Over the years, and as the range of evaluation theories has continued to grow, evaluation scholars and practitioners have developed various visualized classification frameworks of evaluation theory, invoking images such as trees, rivers, the periodic table, metro maps, concept maps, and most recently gardens.